Construction of a WBGT index meter using low cost devices - Varela-Aldás, José (2020)
Appropriate working conditions can improve the working performance of an employee on a company, one of the main concerns nowadays is the thermal stress, due to the affection not only to the productivity of an employee but also for the risk of affections to his health, in this sense, WBGT (Wet-Bulb Globe Temperature) index is widely proved to define thermal discomfort and thermal stress but in some cases is out of reach due to its cost or availability on a certain region of the world, so this work explains the construction of a low cost device WBGT meter built by an Arduino pro mini, three lm35 temperature sensors and an LCD to install the electronic system; Globe temperature and wet bulb temperature was achieved using a matte black sphere and moistened fabric, respectively. After testing the dispositive, the collected information was sent to a computer through serial communication for further analysis which showed acceptable errors on the measurement of the WBGT index taken indoors and outdoors thru the device and compared to the data obtained by a commercial WBGT meter. © Springer Nature Switzerland AG 2020.